What Kind of Disagreement Favors Reason-Giving? Analyzing Online Political Discussions across the Broader Public Sphere. (February 2021) - Maia, Rousiley CM; Hauber, Gabriella; Choucair, Thais; Crepalde, Neylson JB
This study adopts a systemic approach, focusing on real-world online discussions in legislative-, media-, and activist-based forums, to explore a set of factors that affects reasoned disagreement in digital environments. While conventional analysis investigates the effects of disagreement on civic and political participation, this study unpacks forms of disagreement that retain a principled link with reason-giving. Our findings demonstrate that context matters for shaping online communication, but that other variables have even stronger correlations. Specifically, moderating disagreement—conceptualized as a way of disagreeing that nevertheless signals a background of agreement in the conversation—strongly increases the likelihood of justificatory behavior, and it does so in more categories than bold disagreement. In conclusion, we argue that forms of disagreement and their respective consequences deserve more empirical and normative attention, not only to advance debates on deliberation but also to critically understand the communicative complexities in a new media landscape.